Favored hydrogenation of linear carbon monoxide over cobalt loaded on fibrous silica KCC-1. (20th March 2020) - Fatah, N.A.A.; Jalil, A.A.; Triwahyono, S.; Yusof, N.; Mamat, C.R.; Izan, S.M.; Hamid, M.Y.S.; Hussain, I.; Adnan, R.H.; Abdullah, T.A.T.; Nabgan, W.
Abstract: In this study, the conversion of CO into CH4 was investigated utilizing a series of cobalt loaded on fibrous silica (KCC-1) catalysts (Co loading of 5–30 wt%), that were synthesized via microemulsion and impregnation techniques. FESEM-EDX and N2 physisorption demonstrated that the KCC-1 possessed a spherical structure with fibrous silica dendrimeric morphology with a superior surface area of 861 m 2 g -1 . A significant decreased in the catalyst surface area was noticed upon the addition of Co, suggesting a possible occurrence of KCC-1 pore blockage. Inversely, the number of basic sites on KCC-1 was enhanced after the incorporation of Co, as observed by pyrrole adsorbed FTIR. At 523 K, bare KCC-1 exhibited a very low activity for CO methanation due to low basicity and the absence of surface active sites. The 20Co/KCC-1 demonstrated the best catalytic performance with 72.7% yield of CH4 and 6.8% of CO2 . These results were plausibly attributed to the high intrinsic number of basic sites and high dispersion of Co on KCC-1 support. A detailed in-situ FTIR spectroscopy study revealed that both types of associative and dissociative mechanism pathways significantly contributed to the high catalytic methanation activity. In addition to the dissociative mechanism, the linear CO species adsorbed on the Co metal by associative mechanism was also further hydrogenated to obtain the final CH4 products. Graphical abstract: Image 1 Highlights: Highly dispersed Co on KCC-1 enhanced the catalytic activity of CO methanation. 20Co/KCC-1 catalyst exhibited the highest activity on CO methanation. High intrinsic basicity of 20Co/KCC-1 enhanced the activity of CO methanation. The 20Co/KCC-1 undergoes both types of associative and dissociative mechanism. Linear CO species on Co metal contributed to high CH4 products.